Penerapan Enkripsi End To End Pada Keamanan Surat Elektronik Di Instansi Militer : Rekayasa Keamanan Siber - irfannugroho irfannugroho; Desyderius Minggu; Yohanes Dwi Cahyono (Jurnal Telkommil, 2026)
The exchange of electronic mail within military institutions requires a high level of security due to the confidential nature of the information transmitted. This research focuses on applying end-to-end encryption (E2EE) technology to enhance the security of electronic mail used in military environments. The applied method includes system design, encryption process implementation, and performance testing to assess encryption reliability and message delivery accuracy. The results indicate that E2EE implementation successfully ensures that messages can only be accessed by the intended recipient, thus preventing unauthorized access during transmission. This study concludes that applying E2EE can effectively improve the confidentiality and security of electronic mail communications within military institutions.